ISU PEMANASAN GLOBAL PADA PERGESERAN PARADIGMA STUDI KEAMANAN DALAM HUBUNGAN INTERNASIONAL - Limbong, Roy (Universitas Perrtahanan Indonesia (UNHAN), 2021)
This article describes a paradigm shift in security studies through the International Relations (HI) approach, which over the years International Relations has focused its discussion on the political-military theme, where the state is the main actor in this study. This tradition is known as realism. Over time, the golden age of the realism paradigm came to an end becauseit was unable to solve the complex problems facing the international community. That is why HI has begun to broaden and deepen the object of discussion into non-military topics, such as economy, politics, social and the environment. In short, HI's discourse moves from state security to human security. As already explained, the economy is one of the areas that has received the most attention because this theme is related to human activities in meeting their basic daily needs. However, this activity has an unwanted impact on the environment, suchas global warming which must be addressed as soon as possible. This prompted the international community to start paying attention to this issue in the last decade. Global warming as one of the biggest problems in environmental security is the trigger. This topic also makes environmental issues the focus of studies on HI approaches and other aspects, such as defense, security, economics and politics.Keywords: International Relations, security studies, environmental issues.